IDEOLOGI PESANTREN SALAF: DERADIKALISASI AGAMA DAN BUDAYA DAMAI - Syamsul Ma’arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
The emergence of a number of religious sects which culminated in violence, especially in Indonesia sometimes dragging the name of the salaf pesantren, is actually a phenomenon that is motivated by a number of determinant factors, such as economic factors, politics and ideology. For the first and second factor has been widely discussed by experts/ researchers, while the ideological factor often forgotten by many people. Whereas the issue of ideologythat believed by each religious groups usually determine their direction and purpose. In fact, sometimes leads to an attitude/decision how to look to other groups. The streams of radical ideology has encourages the hostility with the others. This phenomenon of course reversed with the mainstream ideology of pesantren salaf, one of which is a Pesantren Edimancoro Salatiga. as the result of research revealed that the idiology of this pesantren salaf, always talking mutualrespect and love for fellow human beings, voice for justice, liberation and against any anarchism is an enemy of every religion.